INFLUENCE OF SOIL FACTORS ON PLANT GROWTH AND DEVELOPMENT (Web of Teachers: Inderscience Research, 2026)
Soil is the primary medium that provides plants with water, mineral elements, oxygen, and conditions for root system development. The aim of this article is to analyze the influence of physical, chemical, and biological soil factors on plant growth and development. Mechanical composition, structure, moisture, temperature, acidity, humus content, mineral nutrition, salinity, and soil microflora activity are considered. It is shown that optimal soil conditions enhance root growth, photosynthesis, plant resistance to stress, and productivity, whereas salinization, compaction, moisture deficiency, and pH imbalance reduce the intensity of physiological processes.